Nemo dat rule in Nigeria: charting the path for reform in sale of goods (2012)
This paper addresses the problem associated with transfer of goods by a non-owner in order to develop a suitable mechanism to address the problem. It confirms that the attempts made to resolve the problem equitably between the two conflicting parties has not been an easy task because of the jurisprudential and ideological leanings relating to the dispute. After a critical examination of the nemo dat rule and its exceptions, it posits that contrary to the argument of some scholars, sale made by a non-owner with the authority and consent of the owner is not an exception to the nemo dat rule. It recommends a consumer protection approach as a suitable mechanism that can be adopted in adjudicating and regulating disputes between the owner of goods and the innocent buyer in good faith. The benefit of the approach is that it recognizes the general rule but supports recourse to a suitable exception if the facts of a particular case justify it; thus no interest of any party is deliberately jettisoned.